ASSET YANG MASIH DIJADIKAN AGUNAN BANK DIBERIKAN OLEH PENDIRI YAYASAN DENGAN SURAT PERNYATAAN SEBAGAI KEKAYAAN AWAL YAYASAN - Tinton Hariyanto; Nynda Fatmawati (HUKMY : Jurnal Hukum, 2022)
The initial wealth of foundation establishment as outlined in thedeed made by a notary must be written in the form of money accompanied by a statement of separation of assets of the founder and the preparation of the statement of separation of assets is the founder's obligation so that the founder has a commitment not to interfere in the assets of the foundation, but this becomes a dilemma when the founder does not have enough money to be deposited into the Foundation's treasury as the initial wealth, especially for operations, purchase of inventory and renovation of buildings. The initial wealth of the establishment by using a statement letter of separation of personal assets of the founder of the foundation by valuing the asset with money and the fastest solution is to get ad funds. is in debt to a bank with land and buildings as collateral that is tied to a Mortgage guarantee institution, asset ownership that has not been renamed to the name of the foundation, it’s a problems if the founder does’nt have good intentions to pay off the debt to the bank or hand over the assets. after it is paid off to the Foundation, therefore the Foundation should immediately ask a notary to not only make a deed of establishment of the Foundation but also make a deed of agreement on the transfer of rights either as a grant or waqf along with a deed of power to reverse the name on behalf of the foundation.